2016
DOI: 10.1371/journal.pone.0159544
|View full text |Cite|
|
Sign up to set email alerts
|

Cutaneous Respirometry as Novel Technique to Monitor Mitochondrial Function: A Feasibility Study in Healthy Volunteers

Abstract: BackgroundThe protoporphyrin IX-triplet state lifetime technique (PpIX-TSLT) is proposed as a potential clinical non-invasive tool to monitor mitochondrial function. This technique has been evaluated in several animal studies. Mitochondrial respirometry allows measurement in vivo of mitochondrial oxygen tension (mitoPO2) and mitochondrial oxygen consumption (mitoVO2) in skin. This study describes the first use of a clinical prototype in skin of humans.MethodsThe clinical prototype was tested in 30 healthy volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 34 publications
4
36
2
Order By: Relevance
“…The “canary” function of human skin in relation to organ function still needs further investigation but important is that also changes in cutaneous mitochondrial oxygen consumption correlate with ODR changes in other organs and tissues [ 17 ]. The ODR from the dynamic measurement 6.3 mmHg s −1 in this example corresponds with previous data from healthy volunteers 5.8 ± 2.3 mmHg s −1 [ 29 ] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The “canary” function of human skin in relation to organ function still needs further investigation but important is that also changes in cutaneous mitochondrial oxygen consumption correlate with ODR changes in other organs and tissues [ 17 ]. The ODR from the dynamic measurement 6.3 mmHg s −1 in this example corresponds with previous data from healthy volunteers 5.8 ± 2.3 mmHg s −1 [ 29 ] .…”
Section: Discussionsupporting
confidence: 86%
“…Till now the feasibility of measuring mitoPO 2 and mitoVO 2 with PpIX-TSLT was tested in healthy volunteers [ 29 ] and is currently further evaluated with COMET in the perioperative setting. However, the original main development idea of COMET was the in vivo determination of aspects of mitochondrial (dys)function in critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…However, it needs to be confirmed that MID patients with involvement of the skin indeed show abnormal mito-pO 2 or mito-VO 2 on cutaneous respirometry. In a study of 30 healthy controls, reference limits of mito-pO 2 are given as 44 ± 17 mm Hg, and those of mito-VO 2 as 5.8 ± 2.3 mm Hg at 34 degrees Celsius [ 24 ]. The study showed that cutaneous respirometry allows measurement of mitochondrial oxygenation and oxygen consumption in humans [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spectroscopic approaches, including broadband spectroscopy, allowed for measurement of the oxidative state of cellular cytochromes which reflect cellular energetics [ 32 , 33 ]. Measurement of cutaneous mitochondrial PO 2 , utilizing the oxygen-dependent delayed fluorescence of protopor-phyrin IX in the skin [ 34 , 35 ], has been used to assess the mitochondrial PO 2 response to acute hemodilution in an experimental pig model [ 35 ]. This approach was able to detect tissue hypoxia at an earlier stage of hemodilution relative to more traditional measurements including changes in MAP, serum lactate, VO 2 , and NIRS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%